Dissection of intratumor microbiome–host interactions at the single-cell level in lung cancer - Yong-Jing Ma; Yuan-Chen Sun; Lu Wang; Wan-Xing Xu; Xiao-Dan Fan; Jun Ding; Christopher Heeschen; Wen-Juan Wu; Xiao-Qi Zheng; Ning-Ning Liu (hLife)
The intratumor microbiome, one of the hallmarks of cancer, plays a crucial role in cancer progression through its interaction with the host. However, the underlying mechanisms remain poorly understood. In this study, six publicly available single-cell transcriptomic lung cancer datasets (comprising 178 samples) from multiple centers (Shanghai, New York, Seoul) were integrated to investigate the heterogeneity of host–microbiome interactions at the single-cell level using single-cell analysis of host–microbiome interactions (SAHMI). The results indicate that primary tumor tissues have a high proportion of fungi-associated cells, whereas metastatic brain tissues predominantly contain bacteria-associated cells. There are also distinct microbial distributions across cell types. Notably, the presence of specific bacteria significantly influences the transcriptome of resident host cells, including T cells and macrophages, by modulating pathways related to ribosomal RNA (rRNA) processing, cellular responses to stress and stimuli, and RNA and protein metabolism. Finally, specific cell-associated bacteria are significantly correlated with clinical features, such as lung cancer stages and smoking frequency. These single-cell insights into microbiome–host interactions improve current understanding about lung cancer development and progression and offer potential micro-ecological and diagnostic insights.